Dinamika Garis Kemiskinan dan Tingkat Kemiskinan 10 Provinsi di Indonesia Tahun 2015-2024 - Ari Maulana; Fasha Siti Fatimah; Ihda Aulia Mutmainah; Ismi Marhamah; Wanda Hamidah; Apip Supriadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of inflation, Gross Regional Domestic Product (GRDP), and the Provincial Minimum Wage (PMW) on the poverty line in 10 provinces in Indonesia. The research employs a quantitative approach using panel data regression analysis. The data utilized in this study consist of panel data covering a 10-year period, from 2015 to 2024, obtained from the Provincial Offices of Statistics and Statistics Indonesia (Badan Pusat Statistik/BPS). To examine the relationship between variables across regions and over time, the fixed effect model is applied in the analysis. The results of the analysis indicate that inflation and GRDP do not have a statistically significant effect on the poverty line in the 10 provinces examined. These findings suggest that although inflation and GRDP are important macroeconomic indicators, their variations during the study period were not sufficient to directly influence changes in the poverty line across the provinces. In contrast, the Provincial Minimum Wage (PMW) is found to have a significant effect on the poverty line. This result implies that increases in the minimum wage play a crucial role in improving household purchasing power, which can contribute to reducing poverty levels. Overall, the findings highlight the importance of wage policy as an effective instrument for poverty alleviation at the provincial level. While broader economic growth and price stability remain important, policies related to minimum wage determination appear to have a more direct and measurable impact on poverty conditions. Therefore, policymakers are encouraged to consider wage policies alongside other macroeconomic strategies to achieve more effective poverty reduction outcomes.